α-1 acid glycoprotein inhibits insulin responses by glucose oxidation, protein synthesis and protein breakdown in mouse C2C12 myotubes - T.G. Ramsay; L.A. Blomberg; T.H. Elsasser; T.J. Caperna (Animal, 2019)
Increased plasma α-1 acid glycoprotein (AGP) is correlated with reduced growth rates in neonatal swine. The specific physiological mechanisms contributing to this relationship are unknown. This study was performed to determine if AGP can modify muscle metabolism by examining glucose oxidation and protein synthesis in the C2C12 muscle cell line. Cells were used for experiments 4 days post-fusion as myotubes. Myotubes were exposed to AGP for 24 h, with the last 4 h used to monitor 14C-glucose oxidation or to measure protein synthesis by incorporation of 3H-tyrosine. Treatment of C2C12 myotubes with mouse AGP (100 µg/ml) reduced glucose oxidation (P<0.01, n=3 trials), whereas bovine insulin (1 µM) stimulated glucose oxidation (P<0.05, n=3 trials). Treatment with AGP in combination with insulin reduced 14C-glucose oxidation (P<0.05, n=3 trials), similar to the effect of AGP alone. Glucose transport, as measured by 3H-deoxyglucose uptake, was increased by 38% with 1 µM insulin (P<0.05, n=3 trials), whereas AGP alone increased glucose uptake by 36% (P<0.05, n=3 trials). The combination of insulin and AGP in the medium resulted in an 88% increase in glucose uptake (P<0.01, n=3 trials). Protein synthesis was measured by 3H-tyrosine incorporation into C2C12 myotubes. Insulin stimulated a 18% increase in 3H-tyrosine incorporation (P<0.05, n=6 trials). The incorporation of 3H-tyrosine into myotubes was reduced by 20% with AGP incubation (P<0.01, n=6 trials), like the 20% decrease in 3H-tyrosine incorporation in response to the combination of AGP and insulin (P<0.01, n=6 trials). Protein breakdown, as measured by the release of 3H-tyrosine from C2C12 myotubes, was reduced 27% by insulin (P<0.01, n=6 trials). Treatment with AGP had no effect on protein breakdown (P>0.05, n=6 trials), whereas incubation with both AGP and insulin reduced 3H-tyrosine release by 15% (P<0.01, n=6 trials). First, these data indicate that the acute phase protein AGP can interact with the skeletal muscle to reduce glucose oxidation, but this is not the result of an effect on glucose transport. Second, AGP can specifically reduce protein synthesis. Lastly, AGP can inhibit insulin-stimulated glucose oxidation, protein synthesis and breakdown.